Preventive Resolution of Labor Disputes - Rymanov, Alexander; Bocharova, Irina (International Journal of Contemporary Economics and Administrative Sciences, 2019)
The paper covers the contradictions in industrial relations and the modern ways of resolving them in Russia. Particular attention is paid to preventive resolution as the least controversial, allowing reducing or eliminating the possibility of a conflict within the labor sphere, as a fair and effective method that reduces the burden on civil courts in conditions of limited budget spending. It is advisable to give priority to out-of-court methods for resolving labor disputes, to direct efforts to prevent the emergence of labor conflicts. Implementation of this strategy should be carried out at the macro– and micro levels. The study shows that in order to increase the efficiency of labor inspection in the Russian Federation in the context of limited budgetary sources of funding, there is a need to expand the scope of activities of the Office of State Supervision in the Sphere of Labor. It is also advisable to adjust the priority activities of the labor inspections, mainly in the direction of the implementation of preventive activities. This will lead to the prevention of conflict situations in the organizations, to ensure the improvement of the enforcement of legislation, contracts and labor agreements. In order to work out effective directions, the article summarizes international experience, best practices in the preventive activities of labor inspections in developed countries and in emerging markets.